Variety of urban design at a new stage - Kiseleva Татьяна; Sadykova Жанна (Рroblems of engineering and professional education, 2023)
The flexibility of the network structure, which allows taking into account changes in the development of the education industry and meeting the needs of various social groups of the population, is achieved through the correct choice of the nature of the location, specialized educational institutions in the planning structure of the city. The location of these facilities, connected by convenient transport communications with all parts of the city, will expand and complement their functions, bringing them to the level of inter-district general educational services.